Path to global inflence:conditions for chinese film industry to succeed - YU, Dong (Institutional Knowledge at Singapore Management University, 2021)
The world has undergone tectonic transformations since the onset of the coronavirus pandemic. Inevitably, the pandemic created the perfect conditions for the acceleration of digitization and new infrastructural technologies aimed to increase the speed and availability of content. In China, the pandemic forcedmajor releases to be streamed via online platforms and drastically altered consumer’s perception of the quality of digital content. Most importantly, digital streaming has shown huge capitalization potential, aided by the spread of 5G technologies, as those who embraced online platforms thrived in the midstof the global pandemic. During the course of this dissertation, the Chinese film industry had undergone significant transformations, including but not limited to stringent enforcement of policies aiming to regulate content and the rapid expansion of streaming technologies. In parallel, I have put in best efforts to share my analysis and viewpoint on how the industry needs to be conditioned to reach the status of a global film powerhouse. The aftermath of the pandemic in China has seen a rebirth of the entire industry with an eager consumer audience ready to embrace films as a source of collective mental healing, begging the question, “can the Chinese film industry finally receive the type of global recognition that Hollywood hasstarted taking for granted?” While the Chinese film industry has thrived, for it to truly become a global film powerhouse requires that five critical conditions be met, namely film content globalization, censorship / rating system, greenlight process, talent training / development, and streaming. Structurally, I will give an overview of the five critical conditions and evaluate the current Chinese film industry against these five specific benchmarks with comparative studies and insightful analysis from managing my own company, Bona Film Group.